Drug resistance to delamanid was detected in susceptible tuberculosis patient in Russia - Platon Eliseev; Irina Vasilyeva; Anatoly Vinokurov; Evgeny Kuznetsov; Kirill Baibekov; Anastasia Kazulina; Anastasia Samoilova (Journal of Global Antimicrobial Resistance, 2024)
AIM: To detect mutations in M. tuberculosis (MTB) associated with delamanid drug resistance in patients with tuberculosis (TB) in Russia. BACKGROUND: Delamanid is important in treatment of multi- and extensively drug-resistant TB. Reports on delamanid drug resistance are increasing making it necessary to perform drug susceptibility testing (DST). METHODS: In 2023 full-genome next-generation sequencing (NGS) and DST of 364 MTB isolates from TB patients in different regions of Russia were performed. RESULTS: Drug resistance to delamanid was detected in five MTB isolates. In all 5 isolates mutations in the gene ddn Trp88* (tGg > tAg) were detected. Resistance was confirmed by Bactec MGIT DST with critical concentration 1.0 μg/mL. Interestingly, one isolate with drug resistance to delamanid was susceptible to other drugs (Table). Four other isolates had different combinations of drug resistance to rifampicin (rpoB Ser450Leu), isoniazid (katG Ser315Thr), ethambutol (embB Asp354Ala), streptomycin (rpsL Lys43Arg), pyrazinamide (pncA Asp63Ala), ethionamide (ethA 1614del and ethA 1615del), amikacin and capreomycin (rrs 1401A>G), moxifloxacin (gyrA Asp94Gly and gyrA Asp94Ala), para‐aminosalicylic acid (folC Glu40Gly) and cycloserine (ald 130dupG). Drug resistance to bedaquiline and linezolid was not detected in those isolates. CONCLUSION: Drug resistance to delamanid was detected in patients that were not previously exposed to delamanid, including one patient without any additional drug resistance suggesting that all patients should be tested for drug resistance before treatment initiation regardless of their treatment history.